ASPIRATIONAL SELF-LABOUR AND LISTENING PRACTICES IN BRAZIL - Dalpizol Valiati, Vanessa Amália; Prey, Robert (AoIR Selected Papers of Internet Research, 2026)
Music has long been understood as performing a dual role: an active agent (De Nora, 1999) capable of eliciting physiological and psychological transformations and, simultaneously, a resource that can be used to signal distinction (Bourdieu, 1984). In this sense, this paper asks: How do contemporary users of social media and streaming platforms employ music and the affordances of music platforms to transform themselves? To answer this question, we introduce the concept of aspirational self-labour to examine how contemporary music listeners engage with online music platforms as part of their self-transformation efforts. Drawing from an interdisciplinary body of literature, we explore how users navigate the dual nature of music as both agent and resource in their everyday lives. By integrating concepts from social reproduction theory (Drott, 2023), self-expansion models (Aron & Aron, 1986), and aspirational labour (Duffy, 2016), we propose a nuanced framework for understanding the labour involved in curating, discovering, and sharing music in digital environments. Through semi-structured walk-through interviews with 25 young music listeners in Porto Alegre, Brazil, we analyse how these individuals strategically engage with music as a tool for motivation, self-improvement, and social positioning. Music specifically produced for such uses and engaged in through this listening mode is typically dismissed as ‘functional’. We argue that scholars need to move beyond this simplistic portrayal of what is, in fact, a complex dual (agent-resource) mode of using music. Instead, we propose a richer conceptual vocabulary to understand one approach to listening through online platforms.